Pengaruh model geometris ruang plafon terhadap tahapan ignition dan flashover pada kebakaran rumah tinggal di pemukiman padat - Amat Rahmat (ARTEKS : Jurnal Teknik Arsitektur, 2022)
As an artificial physical place, residential building is formed by various functional spaces, such as residential space and the space between the ceiling space and the roof, i.e. the attics. The phenomenon of fires in residential buildings in densely populated areas is suspected of having occurred in the attics. Hitherto, research on the fire space model concerning the stages of ignition and flashover usually employs the Steckler's compartment model in the form of a cube/box. On the contrary, the fire model with a triangular roof shape is still rarely studied. The purpose of this study was to analyse the influence of the geometric shape of the attics on the ignition and flashover stages in residential fires located in densely populated settlements. This study employs an experimental method by conducting scaled experiments of the geometric model of the ceiling space in the form of a triangular gable roof and shed roof, focusing on the ignition and flashover stages. The results showed that the ignition stage in the gable roof and shed roof models occurred in the 3rd and 4th minutes with a temperature ranging from 270 ⁰C- 476 ⁰C. The flashover stage also occurred in the 5th to 9th minute with regular results close to 500 ⁰C.